(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
There are many types of cherry plum (cherry) on our territory of Uzbekistan. There are many types of it, especially in mountainous areas. Therefore, if you think about its beneficial healing properties.